Evaluation and Optimization to Recycle Used TiO2 Photoelectrode for Dye-Sensitized Solar Cells - Ruei-Tang Chen; Chien-Feng Liao (International Journal of Photoenergy)
This study proposes a method for recycling and activating the titanium oxide (TiO2)/fluorine-doped tin oxide (FTO) photoanode in dye-sensitized solar cells (DSCs) by repeated dye adsorption and desorption processes using various desorption agents. This simple and convenient method could be utilized to activate TiO2 photoelectrodes for DSCs after the long-term operation. The devices are immersed in acidic, alkaline, and neutral media of various concentrations for desorption and then are soaked in the N719 solution again. The optimal device had an overall power conversion efficiency (AM 1.5 G, 100 mW/cm2) with 5 × 10−3 M NaOH solution as a desorption agent being 6.44% better than that of devices that had not undergone recycling and activation.